2022
DOI: 10.1186/s13045-022-01285-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of N7-methylguanosine (m7G) in cancer

Abstract: N7-methylguanosine (m7G), one of the most prevalent RNA modifications, has recently attracted significant attention. The m7G modification actively participates in biological and pathological functions by affecting the metabolism of various RNA molecules, including messenger RNA, ribosomal RNA, microRNA, and transfer RNA. Increasing evidence indicates a critical role for m7G in human disease development, especially cancer, and aberrant m7G levels are closely associated with tumorigenesis and progression via reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 87 publications
(148 reference statements)
0
113
0
Order By: Relevance
“…The comparison of the mutations between the subgroups showed a higher TMB in the high-risk group than the low-risk group, as well as some oncogenes, including KRAS ; also, the survival probability in high TMB was better, especially for those with a low-risk level ( Figure 8 ). Reportedly, m7G could reshape the microenvironment, especially the immune cell infiltration ( 15 ). Combined with functional analyses, we further compared the enrichment scores of 16 types of immune cells and the activity of 13 immune-related pathways between the low and high-risk groups employing ssGSEA.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of the mutations between the subgroups showed a higher TMB in the high-risk group than the low-risk group, as well as some oncogenes, including KRAS ; also, the survival probability in high TMB was better, especially for those with a low-risk level ( Figure 8 ). Reportedly, m7G could reshape the microenvironment, especially the immune cell infiltration ( 15 ). Combined with functional analyses, we further compared the enrichment scores of 16 types of immune cells and the activity of 13 immune-related pathways between the low and high-risk groups employing ssGSEA.…”
Section: Resultsmentioning
confidence: 99%
“…M7G modification is one of the most common forms of base modification in post-transcriptional regulation. It is widely distributed among tRNA, rRNA, and the 5′ cap of eukaryotic mRNA, and plays an important role in 'RNA processing, metabolism, stability, and nucleation, as well as translation (9)(10)(11). Previous studies have found that m7G tRNA modification enhances oncogenic mRNA translation and promotes the progression of intrahepatic cholangiocarcinoma (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed among tRNA, rRNA, and the 5′ cap of eukaryotic mRNA, and plays an important role in 'RNA processing, metabolism, stability, and nucleation, as well as translation (9)(10)(11). Previous studies have found that m7G tRNA modification enhances oncogenic mRNA translation and promotes the progression of intrahepatic cholangiocarcinoma (9). However, few studies have verified whether m7G-related genes play a key role in GC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…m 7 G is an abundant modification found in the 5′ guanosine cap of mRNAs, as well as internally in mRNAs, tRNAs, rRNAs, and miRNAs [ 102 ]. m 7 G is critical for the complete maturation of the 5′ guanosine cap found in all RNAs transcribed by RNA pol II [ 103 ].…”
Section: The Epitranscriptome In Rnamentioning
confidence: 99%